Les relations entre les structures situationnelles et les sources de conceptualisation dans le fait divers - Miczka, Ewa (Neophilologica, 2019)
In this paper the author analyzes the relations between situational structures and sources of conceptualization in fait divers. Situational structures of discourse are defined as a sequence of experiential frames. Each frame permits to conceptualize one event forming part of information introduced in the discourse. The author focuses her attention on two classes of situational structures: (1) with one possible scenario or (2) with two or more scenarios of the same event suggested in the discourse and then the analysis of sources of different conceptualizations is carried out.